2017
DOI: 10.1103/physrevlett.119.163401
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Stopping of Slow Protons in Oxides: Scaling Properties

Abstract: Electronic stopping of slow protons in ZnO, VO2 (metal and semiconductor phases), HfO2 and Ta2O5 was investigated experimentally. As a comparison of the resulting stopping cross sections (SCS) to data for Al2O3 and SiO2 reveals, electronic stopping of slow protons does not correlate with electronic properties of the specific material such as band gap energies.Instead, the oxygen 2p states are decisive, as corroborated by DFT calculations of the electronic densities of states. Hence, at low ion velocities the S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 55 publications
8
32
0
Order By: Relevance
“…[38], a Gd-oxide surface layer does not give rise to significant deviations from such a velocity proportionality of proton stopping even down to v = 0.15. This is in accord with other searches for such deviations in oxides [39], where only a faint influence of a gap might be visible at proton energies above 2 or 3 keV. Thus, it seems that either strong perturbations or also quasimolecular effects might open many electron-reaction channels that allow for a quasifree electronic motion during atomic interaction processes.…”
Section: Discussionsupporting
confidence: 89%
“…[38], a Gd-oxide surface layer does not give rise to significant deviations from such a velocity proportionality of proton stopping even down to v = 0.15. This is in accord with other searches for such deviations in oxides [39], where only a faint influence of a gap might be visible at proton energies above 2 or 3 keV. Thus, it seems that either strong perturbations or also quasimolecular effects might open many electron-reaction channels that allow for a quasifree electronic motion during atomic interaction processes.…”
Section: Discussionsupporting
confidence: 89%
“…hereafter)] has been relatively well understood within linear response [5][6][7] and non-linear response formalisms [8][9][10][11]. The linear and non-linear response approaches have been refined [12][13][14][15][16][17][18][19] but essentially remained limited in their practical applicability to simple metals and simple ions [20,21].…”
mentioning
confidence: 99%
“…Recent studies on the interaction of ions with solids in the very-low-energy range have produced new and relevant insights in various aspects of the interaction process, including nonlinear screening and band-structure effects [1][2][3][4][5][6]. In a recent work using light and heavy ions on a TiN target, Sortica et al [7] observed a striking discrepancy in the values of the electronic stopping cross section when compared with the standard predictions of the density functional theory (DFT) [8,9].…”
mentioning
confidence: 99%